More cercospora species infect soybeans across the Americas than meets the eye - Soares, Ana Paula Gomes (2015)
Fil: Soares, Ana Paula Gomes. Universidade Federal de Viçosa. Departamento de Bioquímica e Biologia Molecular . Viçosa (MG), Brazil.